Using Physical and Chemical Methods to Improve the Nutrient Quality of Dragon Fruit (Hylocereus polyrhizus) Peel for Use as Feed for Laying Hens - Mahlil, Yusuf; Husmaini; Warnita; Mirzah; Mahata , Maria Endo (International Journal of Poultry Science, 2018)
Background and Objective: The processing of dragon fruit (Hylocereus polyrhizus) into a food product leaves fruit peel waste, which is a potential feed for laying hens. Dragon fruit peel contains phytochemical compounds such as anthocyanins, beta-carotene and lycopene, which are reported to have antioxidant functions and to lower cholesterol in blood serum. Previous study showed that the problem with using dragon fruit peel as feed for laying hens was due to its high content of crude fiber, which inhibited the amount of its utilization in the poultry diet and lowered its phytochemical absorption in the digestive tract. Physical and chemical methods, such as steaming and soaking in acid solution, could reportedly degrade and lower the crude fiber content in feed containing high levels of crude fiber. The goal of this study was to evaluate the nutrient content of dragon fruit peel, particularly its crude fiber content, after processing with physical and chemical methods, to determine its use in feed for laying hens. Materials and Methods: The dragon fruit peels in this experiment were collected from local restaurants in Indonesia. The experiment consisted of 2 parts. In part one, dragon fruit peels were steamed in boiling water at a temperature of 98°C. It was performed in a completely randomized design, with different steaming times (0, 5, 10, 15 and 20 min) and each treatment was replicated 4 times. Then the dry matter, crude fiber and crude protein were measured. In the second part, the dragon fruit peels were treated by soaking in 7.5% acetic acid (pH 4). The experiment was performed in a completely randomized design with different soaking times (0, 2, 4, 6 and 8 h) and each treatment was replicated 4 times. The dry matter, crude fiber and crude protein were measured. Results: The experiment showed that both the physical and chemical methods highly significantly reduced the crude fiber content of dragon fruit peel (p0.05). Conclusion: Processing dragon fruit peels by using a physical method (steaming for 20 min) and a chemical method (soaking in acetic acid solution for 4 h) lowered the crude fiber content in dragon fruit peel from 24.01-19.81% and from 24.01-20.39%, respectively, without altering the protein and dry matter content of dragon fruit peel.